(3efGaY GdCMLGQ hGdNQRs - (3YWGA Hf eMeO GdMGSHs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdeDda QMeg Gddg JYGdi cfJ fXQJ ai cJGH GdHQGHi hGdCMLGQ dgQeS GdMcje ai eUMag GdeYQha HGQMGfjbi GdLGeY dPcQ GdCMLGQ hGdCTLGQ hGdWjQ hGdMjhGf s
(3BNQgG (B:s
(3hjUH YdjgG eGA hjSbi ddYGTb efg ajdShG hbO PcQfG hHjfG ef GdCMLGQ hGdNQR HMSH eG hLOfG hGdMeO ddg Ydi Pdc cKjQkG hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde hMSHfG Gddg hfYe Gdhcjd s
(3ChQGb GdcJGH eVWQHI ai GdJLdjO aajgG JbOje hJCNjQs
(3Yf gQeS GdMcje ef eUMag GdeYQha HGQMGfjbi hef cJGH GdWdeSGJ ddMceGA GdSHYIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(3317) s
Keywords: (3GdcjejGA h GdWHjYjGJs